Polydopamine‐Enabled Biomimetic Surface Engineering of Materials: New Insights and Promising Applications - Mohit Saraf; Prateek; Rahul Ranjan; Bhuvaneshwari Balasubramaniam; Vijay Kumar Thakur; Raju Kumar Gupta (Advanced Materials Interfaces, 2024)
Abstract Surface modification is an important approach to modify the properties of materials. Numerous approaches have been adopted to tailor the properties of such materials, which have been proven successful at many scales and parameters. However, most of these techniques are often tedious, poorly adhesive, costly, sometimes hazardous, and surface‐specific, hence cannot be extended on a large scale and all kinds of surfaces. These shortcomings have led to the emergence of new dopamine (DA) based green surface modification technique where a thin polydopamine (PDA) layer is deposited on surfaces through a facile polymerization of DA under alkaline conditions to enable the surface for various applications. This surface modification strategy has several advantages over other techniques in deposition processing under mild conditions, cost‐effective and straightforward ingredients, and applicability to all kinds of surfaces regardless of their sizes, shapes, and types. Moreover, the PDA layer enhances the surface functionality. Therefore, it can serve as a versatile platform for various secondary reactions for a wide range of applications. Herein, the chemistry of DA is summarized and its polymerized form PDA for the modification of different families of materials’ surfaces with an emphasis on energy, environmental and biological applications.